Energy Consumption and Energy Intensity Trends in Transition and Developed Economies - Štreimikienė, Dalia (Ekonomika, 2004)
The article analyses energy efficiency and energy consumption trends in Lithuania in terms of sustainable development and aims to assess these trends in developed and transition economies. The results of development achieved by EU-15 and other developed countries indicate that the goals of sustainable development such as prosperity, high rates of economic development and low impact on the environment are not conflicting and can be achieved together. Transition economies newly entered the EU and suffering from a high resource intensity of economics and a comparatively low income per capita can converge in terms of the main indicators with EU-15 up to 2020.